2017
DOI: 10.1007/s00397-017-1025-0
|View full text |Cite
|
Sign up to set email alerts
|

Linear and non-linear nature of the flow of polypropylene filled with ferrite particles: from low to concentrated composites

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…From Figure 5, it can also be seen that as the strain increased, the storage modulus started to decrease. This is well-known phenomena (also referred to as Payne effect) that is characteristic for filled elastomers, highly filled suspension, and filled polymers [39][40][41][42][43][44][45][46][47][48]. In general, there are two reasons for storage modulus decrease with increasing strain.…”
Section: Strain Amplitude Sweepmentioning
confidence: 99%
“…From Figure 5, it can also be seen that as the strain increased, the storage modulus started to decrease. This is well-known phenomena (also referred to as Payne effect) that is characteristic for filled elastomers, highly filled suspension, and filled polymers [39][40][41][42][43][44][45][46][47][48]. In general, there are two reasons for storage modulus decrease with increasing strain.…”
Section: Strain Amplitude Sweepmentioning
confidence: 99%
“…When the filler content was 50 vol.%, the introduction of dispersing agent shortened the limit of linearity: c was reduced to 0.08% for PP + 50%Sn, and arrived at 0.03% for PP + 50%Sn + SA. This result was in contrast with screening effects exerted by SA among ferrite particles in polypropylene, verified by Rueda et al (2017b). Frequency sweep results were shown for neat and filled PP matrix, up to 50% of Tin particles, with or without SA, in Fig.…”
Section: Rheological Testing On Solid Particles In Polymer-based Compoundsmentioning
confidence: 78%
“…The results showed that compared with pure HDPE, the melt strength of the composites with 2% nano-CaSO 4 is increased by nearly three times, and the tensile strength and elongation at break were increased by 9.16% and 31.43%. Although there are many studies on the application modification of calcium sulfate at present, most of the modification methods are relatively single, and the effect of compatibility with polymer materials after modification is general, 22,23 which limits its application. In addition, the calcium sulfate made from phosphogypsum is more difficult to modify and apply than calcium sulfate whiskers without impurities, so it is of greater significance to find a better modification method for the application of calcium sulfate prepared from phosphogypsum to HDPE.…”
Section: Introductionmentioning
confidence: 99%